Rosenberg, Joseph Elkanah. Wastepaper Modernism: Twentieth-century Fiction and the Ruins of Print - Adhikari, Megh Raj (Literary Studies, 2023)
With new means of communication related to recorded voices and mass-produced images aggressively coming to the forefront, modernist writers remained obsessed and haunted by their alienated, estranged, and disjunct selves reflected in meta-textual forms. Destroyed images of paper in modernist fiction and their connection to growing anxieties about the material form of textual matter provide the focus of Joseph Elkanah Rosenberg’s book Wastepaper Modernism: Twentieth Century Fiction and the Ruins of Print. The book explores premonitions of the ‘death of the paper’ debates well before the invention of the high-tech gadgets that fascinate, and some would say vex contemporary readers via virtual technologies in the digitized e-books and audio books. Having traced its roots to the late nineteenth century, Rosenberg connects anxieties about the imminent breakdown of print and printed matter to the epitome of high-modernist literary experimentation such as typified by James Joyce’s Finnegans Wake.